Perception of HIV/AIDS Prevention Strategies among the Youth in Farming Communities of Osun State, Nigeria. - Famuyiwa, Busayo Solomon (2015)
The study assessed the perception of some selected HIV/AIDS prevention strategies among youths in farming communities of Osun State. It specifically examined their socio economic and demographic characteristics, perception, attitude and practice of the strategies. It further assessed respondents' sources of information, frequency of use and the factors influencing the use of the HIV/AIDS prevention strategies. This was with a view to determining respondents' level of knowledge.